Eosinophilic granuloma of the temporal bone - (:unkn) unknown (My University, 1998)
Eosinophilic granuloma is the benign form of histiocytosis X, or Langerhan's cell histiocytosis. The most frequently affected bones include skull, pelvis, ribs and long bones. Involvement of the temporal bone is a rare manifestation of eosinophilic granuloma. When the disease occurs in the temporal bone, the patient may commonly present acute or chronic otitis media. We report a case of eosinophilic granuloma of the temporal bone presenting with purulent discharge.
Keywords: Eosinophilic granuloma; Temporal bone